A case of acute pancreatitis complicated by acute coronary syndrome - Akgümüş, Alkame; Duygu, Ali (The European Research Journal, 2025)
An inflammatory condition affecting the pancreatic parenchyma is called acute pancreatitis. Alcohol consumption and gallstones are the most frequent etiological factors. Patients with acute pancreatitis can appear clinically in a variety of ways. While individuals with acute pancreatitis may experience ECG abnormalities that resemble acute myocardial infarction, it is uncommon for acute pancreatitis to coexist with actual acute myocardial infarction. Our goal was to present a case of acute pancreatitis exacerbated by acute coronary syndrome. The patient arrived at the emergency room with 60 minutes of epigastric abdominal pain that was prominent there and radiating to the back.